THE COMPOSITION OF NANOPARTICULATE MACKINAWITE, TETRAGONAL IRON(II) MONOSULFIDE - Rickard D.; Griffith A.; Oldroyd A.; Butler I.B.; Lopez-Capel E.; Manning D.A.C.; Apperley D.C. (My University, 2006)
The primary FeS precipitate formed from the reaction between Fe(II) and S(-II) in aqueous solutions at ambient temperatures and pressures is nanoparticulate stoichiometric mackinawite, Fe1.00 ± 0.01S. The material is not hydrated. It is probable that sedimentary mackinawite has this composition. Previous reports of mackinawite compositions of Fe1±xS are incorrect. Mackinawite dissolves in mineral acids to produce rhombic sulfur, the amount of sulfur formed being related to the acid concentration used. The formation of rhombic sulfur, which is not readily soluble in simple mineral acids, leads to poor total recoveries of Fe and S as well as to significant uncertainties in the precision of the analyses. The problem can be overcome by including a reducing agent, such as Ti(III) citrate, in the digestion procedure. Evaporative drying of the material leads to the formation of other contaminants which may be removed by intensive washing and re-suspension of the precipitate or long-term storage in low H2O anoxic environments. Analyses of S(-II) and Fe sulfide species in sediments and natural waters containing FeS using digestion by mineral acids in the absence of a reducing agent are likely to be affected by these results. © 2006 Elsevier B.V. All rights reserved.
Keywords: FES; IRON SULFIDE; MACKINAWITE; SULFIDE